Role of cephalomedullary nail in proximal femur fractures - Kumar, Nishant; Sharma, Dhruv; Kumar, Kuljit (International Journal of Research in Orthopaedics, 2017)
Background: Hip fractures are recognized to be a major public health problem. Key determinants of hip fractures include age, osteoporosis, and falls. In these determinants socioeconomic status, have not been well explored. Under eccentric loading, high bending loads occur, leading to failure of the osteosynthetis anchorage at the center of the femoral head.The introduction of the reconstruction nail has broadened the indications for the intramedullary fixation of difficult femoral fractures. The operative technique is however complicated. Some technical difficulties encountered during its use are presented together with guidance to allow these problems to be avoided. Methods: This Study had included 47 cases which were operated by single surgeon and use of different implant (cephalomedullary nail) was randomized irrespective of fracture types and pattern. This study was done over a period of 12 months (October 2013 to October 2014) with 1 month, 3 months, 6 months, 12 months follow up. At every visit patient were assessed as per Oxford hip score. Type of implant used was PFNA, Intertan, Sirus Nail. Results: The mean age of the patients was 65.68 (±13.55) years. Severe pain was observed among majority of the patients at one month (70.2%) which became mild (40.4%) and moderate (34%) at 3 months. Very mild pain was found in 36.2% patients at 6 months and in 61.7% at 12 months. The limping was all the time among all the patients at one month. However, the limping was found often in 46.8% at 3 months and sometimes in 57.4% at 6 months and 53.2% at 12 months. The hip score was found to be severe among all the patients at one month. However, moderate to severe hip was in 46.8% patients at 3 months, mild to moderate was in 57.4% at 6 months and satisfactory joint function was in 68.1% at 12 months. The comparison of Hip score according to long or short nail at one 3, 6 and 12 months showed no difference. Conclusions: Cephalomedullary nails with adequate technique so that the lag screws by purchase in the centre-centre or posterior-inferior quadrant combines the benefit of sliding hip screw as well as intramedullary implants. So we recommend the use of cephalomedullary nails in proximal femur fractures especially the unstable fractures.